2000
DOI: 10.1073/pnas.240461697
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the neural response to rapid acoustic stimuli in dyslexia: Evidence from functional MRI

Abstract: The biological basis for developmental dyslexia remains unknown. Research has suggested that a fundamental deficit in dyslexia is the inability to process sensory input that enters the nervous system rapidly and that deficits in processing rapid acoustic information are associated with impaired reading. Functional magnetic resonance imaging (fMRI) was used to identify the brain basis of rapid acoustic processing in normal readers and to discover the status of that response in dyslexic readers. Normal readers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
1
22

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(161 citation statements)
references
References 46 publications
11
127
1
22
Order By: Relevance
“…47,48 Figure 3 shows the correct answers in each ear for gap intervals of 2 to 8ms. The percentage of correct answers for these gap intervals are similar in both ears; there was no higher prevalence of correct answers in any one ear.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 Figure 3 shows the correct answers in each ear for gap intervals of 2 to 8ms. The percentage of correct answers for these gap intervals are similar in both ears; there was no higher prevalence of correct answers in any one ear.…”
Section: Resultsmentioning
confidence: 99%
“…In human populations, fundamental deficits in cortical temporal processing affect general hearing and underlie poor language and reading skills (2,(27)(28)(29)(30)(31)(32). In babies, such deficits strongly predict older-age deficits in language and reading abilities (3,33).…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence indicating that the left AC is specialized for processing rapidly changing sounds, regardless of whether speech or nonspeech (10)(11)(12)(13). In support of a causal connection to speech processing, there are a number of studies showing temporal processing deficits in language-impaired children (14,15) or dyslexic adults (16,17), and some of these studies indicate that these deficits can be overcome by training (14,17). Corresponding to the genetic basis of speech and language (18), brain imaging studies showed that in infants a few months old (19) and even in neonates (20), i.e., well before the onset of speech production, there is a left-hemisphere superiority to process specific properties of speech.…”
mentioning
confidence: 99%